COVID-19 and Households Waste in Hispanic America: An Assessment of Trends - Leal Filho, Walter; Lange Salvia, Amanda; Sierra, Javier; Fletcher, Carly A.; Banks, Craig E.; Velazquez, Luis; Anholon, Rosley; Rampasso, Izabela Simon; Mac-Lean Bravo, Claudia Alejandra; Barbir, Jelena; Neiva, Samara (My University, 2022)
The COVID-19 pandemic has caused many social and economic problems in Hispanic America, a region with fragile health and economic systems and many inequalities. The pandemic has negatively influenced various aspects of life and led to changes in various habits and behaviours, including consumption. However, the extent to which the pandemic has influenced households, and waste production, in particular, is not well known. In this context, this paper reports on a study aimed at identifying changes in waste production across households under the special conditions created by the pandemic in Hispanic America. The majority of the respondents stated that their level of satisfaction with waste management policies in their countries did not change much during the pandemic. Only a few stated that they were more satisfied than before. Overall, the results suggest that, like previous crises, the COVID-19 outbreak may generate changes regarding household consumption and waste management in Hispanic America. At the same time, these findings stress the need to improve waste management practices. Some measures that may be adopted to allow Hispanic American countries to better cope with increases in waste production in times of pandemics are listed.
Keywords: covid-19; sustainability; consumption; waste management; behaviour; latin america